Ujaran Kebencian Dalam Penyimpangan Sila Ke-2 Pancasila - Irawan , Aisyah Putri; Irawatie, Aniek; Mulyana , Putri Dina (IKRA-ITH ABDIMAS, 2023)
In the digital age, education is one form of social action centered on social media. The Pancasila concept, which focuses on the right to life, is at the heart of this concept. In Indonesia, there is a significant increase in social media use, with 191 million active social media users as of January 2022. This increase is due to the use of social media, TikTok, Twitter, Facebook Messenger as social learning platforms. Social media use has increased significantly between 2014 and 2022, with 34.2% of Indonesians using social media regularly. Hate speech, a form of communication, is a common problem in the educational world, often involving racial, gender, and ethnic issues. Social media use has also increased in recent years, with the emergence of social media platforms like TikTok and Twitter. The results of this study show that 90% of people claim to have received or engaged in hate speech, both on social media and in everyday life. A large number of them use social media like TikTok, Twitter and instagram. The factors in which hate speech arises are internal factors of the individual’s psychological state, and external factors such as a general group of societies that adhere to primordialism and ethnosentrism. The methods used are librarystudies and quantitative analysis. Qualitative understands the meaning present in the phenomenon of hate speech as a form of simulation of Pancasila’s second hatred. The process of data collection, data analysis, and drawingconclusions is part of the quantitative analysis.